An Adsorption Kinetic and Thermodynamic Study of Dyeing Betacyanin Extract from Dragon Fruit Skin onto the Spun Silk and Acrylic Yarn - Norasiha, Hamid; Mimi Sakinah, A. M. (AENSI Publishing, 2017)
Background: Dragon fruit is one of the plant that can be extracted to be a natural dye. This fruit is contained a betacyanin pigment which can be dyed on to the textile fibers. The natural dye was extracted using water extraction. The betacyanin pigment was applied onto the spun silk and acrylic yarn. Two kinetic models, the pseudo first order model and pseudo-second order model were selected to follow the adsorption process. Kinetic parameters such as rate constant, equilibrium capacities and correlation coefficients for each kinetic equation were calculated and discussed. Objective: The main objective of this study is to evaluate the adsorption and kinetic parameters of dyeing betacyanin pigment extract from dragon fruit skin onto spun silk and acrylic yarn. Result: It was shown that the adsorption betacyanin pigment onto spun silk and acrylic yarn could be described by the pseudo-second order. The rate of constant was increased as temperature increased. The activation energy calculated was 55.7kJ/mol for spun silk and 44.5kJ/mol indicated that the adsorption process was controlled by chemisorption. The thermodynamic parameters such as ΔG°, ΔH° and ΔS° were also calculated. The negative values of ΔG° and ΔH° obtained indicated that the process of adsorption of betacyanin pigment adsorbed onto spun silk and acrylic yarn were spontaneous and exothermic. The values of ΔS° is negative indicated that the randomness of dye molecule distribution was increased as temperature increased. Conclusion: It is concluded that the adsorption of betacyanin pigment onto spun silk and acrylic yarn were favorable and controlled by chemisorption process based on the kinetic and thermodynamic parameters that had been determined.